EFFECT OF ULTRA HIGH TEMPERATURE PROCESSING ON LIPIDS OXIDATION IN MILK-FORTIFIED WITH SOME MINERAL ELEMENTS - Atallah Abdulghani; Mahmood Younis Ali (Mesopotamia Journal of Agriculture)
The hypothesis of the present study was that the Ultra-high temperature (UHT) processing of fluid milk-fortified with Zn, Fe or Mg individually might change the perception of milk flavor as compared to normal UHT milk without fortification. Samples of fortified milk with zinc, iron and magnesium have been processed by a bench-top UHT plant (145 ºC/6 s) and filled into transparent polyethylene terephthalate containers. The milk samples were stored in closed incubator at 30 ºC for 60 days without exposing to light. At 10 and 30 days intervals, the samples were assessed for TBA test and sensory evaluation respectively. The main concern of this work was to evaluate the effect of UHT processing on the level of oxidation by both chemical and sensory evaluation of the fortified milks. Results showed that the values of TBA test increased significantly (p≤0.05) at the end of the storage life (60 d/30 ºC). Sensory evaluation of fortified milks with Zn, Fe and Mg showed miscellaneous results.